Impact of liquidity on profitability in Nepalese Commercial Bank (Patan Pragya, 2019)
This study explores the influence of liquidity on the profitability in the Nepalese commercial banks. 5 commercial banks in Nepal; Agriculture Development Bank, Everest Bank, Prime Commercial Bank, Sunrise Bank and Citizens Bank International are randomly selected among 28 commercial banks of Nepal as a sample and analyzed for the current study over the period 2010/11 to 2016/17 AD. Since liquidity management can increase the bank’s profitability. the study has examined their liquidity management as well as profitability positions using various statistical and financial tools. The article indicates largely zigzag trend of average profitability of commercial banks, although the trend of liquidity ratios of the bank is unstable. The research concluded that bank’s liquidity ratios have below the prescribed standard. Similarly CRR is extremely heavy than prescribed by monetary policy 2016/17. The CRR and IGSCA are positively correlated with ROA while CRR and CBBISD are inversely correlated with ROA. In case of liquidity-ROE Relation, CR is inversely correlated to ROE but all other ratios (CRR, CBBISD and IGSCA) are positively correlated with ROE. It also has reported there is significant relationship between liquidity ratios with profitability, except between IGSCA and ROA.